HUBUNGAN PENGETAHUAN GIZI DAN ASUPAN SERAT DENGAN KONSTIPASI FUNGSIONAL PADA MAHASISWA KEPERAWATAN UNIVERSITAS UDAYANA - Dewi, Kadek Riska Kristyani Sari; Manangkot, Meril Valentine; Krisnawati, Komang Menik Sri (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p05, 2022)
Excessive lifestyle among adolescents has successed to change their diet in consuming fast food. Habit of consumption fast food causes functional constipation. Low nutritional knowledge and fiber intake are factors that affect the functional constipation. This study aimed to investigate the correlation between nutritional knowledge and fiber intake with functional constipation among nursing students. This study was a quantitative study with cross-sectional design. Purposive sampling was used to recruit 52 respondents from March 22 nd until April 10 th , 2021. Data collection was conducted using questionnaires for respondent characteristic, nutritional knowledge, fiber intake based on Recall questionnaire three times a day and functional constipation based on ROME III. Spearmen Rank was used to analyse the data. Based on the result, it showed that there was a moderate and negative correlation between fiber intake and functional constipation (r = 0,572; p = 0,001, ? = 0,05) that means less of fiber intake will make heavier functional constipation among individual. In the other hand, there was not a significant correlation between nutritional knowledge and functional constipation (p = 0,2). Conclusion of this study is nutritional knowledge and fiber intake can affect functional constipation. This study gives a better knowledge among nursing student and pay attention in food consuming that contain fiber so they can prevent functional constipation. Keywords: fiber intake, functional constipation, nutritional knowledge, nursing student